2021
DOI: 10.1088/1361-6528/abe78a
|View full text |Cite
|
Sign up to set email alerts
|

Tuning electrical and interfacial thermal properties of bilayer MoS2 via electrochemical intercalation

Abstract: Layered two-dimensional (2D) materials such as MoS2 have attracted much attention for nano- and opto-electronics. Recently, intercalation (e.g. of ions, atoms, or molecules) has emerged as an effective technique to modulate material properties of such layered 2D films reversibly. We probe both the electrical and thermal properties of Li-intercalated bilayer MoS2 nanosheets by combining electrical measurements and Raman spectroscopy. We demonstrate reversible modulation of carrier density over more than two ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…It has been shown that a pressure as large as 20 GPa is needed to motivate the phase transition from 2H to 2Ha. 51−53 According to the experiment, the 2H-1T phase transition can be induced when the Li intercalation concentration is around 11.8% (Li 0.4 MoS 2 ), 54 which perfectly matches the theoretical calculation, 55 while for the low intercalation concentration of 1% (LiMo 32 S 64 , as used in our simulation), no feature of phase transition from 2H to 2Ha or 1T has been reported in the experiments so far. Thus, in practice, the 2H-2Ha phase transition can be prohibited by the kinetic barrier for our systems, and so here we focus on the 2H phase, and the most stable inserting site for the guest atoms is the regular octahedral site.…”
Section: Stable Configuration Of the Intercalated Vacancy-free Mos 2 ...supporting
confidence: 82%
“…It has been shown that a pressure as large as 20 GPa is needed to motivate the phase transition from 2H to 2Ha. 51−53 According to the experiment, the 2H-1T phase transition can be induced when the Li intercalation concentration is around 11.8% (Li 0.4 MoS 2 ), 54 which perfectly matches the theoretical calculation, 55 while for the low intercalation concentration of 1% (LiMo 32 S 64 , as used in our simulation), no feature of phase transition from 2H to 2Ha or 1T has been reported in the experiments so far. Thus, in practice, the 2H-2Ha phase transition can be prohibited by the kinetic barrier for our systems, and so here we focus on the 2H phase, and the most stable inserting site for the guest atoms is the regular octahedral site.…”
Section: Stable Configuration Of the Intercalated Vacancy-free Mos 2 ...supporting
confidence: 82%
“…Included in this category are electric-double-layer transistors (EDLTs), which are FETs in which the gate oxide is replaced by an electrically insulating but ionically conductive electrolyte. While such a device could also undergo electrochemical reaction under sufficiently large gate voltage, , in this study we consider EDLTs as ionically gated FETs for which electrochemical reactions are absent. As Leighton et al.…”
Section: Introductionmentioning
confidence: 99%